Black Soldier Fly Larval Bioconversion of Fruit and Vegetable Waste: Carbon-Nitrogen Conversion and Estimation of Greenhouse Gas Emissions - Riang Ursada; Ahmed Zuhdi; Arseto Yekti Bagastyo; Arry Febrianto (Jurnal Ilmu Lingkungan, 2025)
Fruit and vegetable waste accounts for approximately 36% of total food waste in Indonesia. The accumulation of this waste in landfills contributes to increasing greenhouse gas (GHG) emissions and environmental pollution through leachate production. Treatment using Black Soldier Fly (BSF) larvae offers an efficient and sustainable alternative, with lower GHG emissions compared to composting or anaerobic digestion. This study aimed to evaluate the bioconversion efficiency of BSF larvae in reducing fruit and vegetable waste (specifically cabbage, water spinach, spinach, mustard greens, watermelon, melon, banana, and papaya) by analyzing the transformation of carbon (C) and nitrogen (N) into larval biomass and residue. Substrate compositions were varied with vegetable-to-fruit ratios of 90:10, 80:20, 70:30, and 60:40 (w/w), and larval densities of 1, 2, and 4 larvae/cm² were tested. Results showed that carbon and nitrogen conversion into larval biomass ranged from 7.92–17.59% and 4.96–21.69%, respectively, while conversion into residue ranged from 22.53–63.75% for carbon and 18.12–80.78% for nitrogen. The substrate with a 90:10 vegetable-to-fruit ratio produced the highest conversion efficiency. The values of Approximate Digestibility (AD), Efficiency of Conversion of Digested Food (ECD), and Efficiency of Conversion of Ingested Food (ECI) ranged from 32.44–74.71%, 17.68–42.96%, and 8.09–18.64%, respectively. The larval survival rates reached 95.61%. Furthermore, BSF bioconversion generated the lowest GHG emissions among all compared waste treatment methods, with a value of 102.27 g CO₂ eq/kg of waste. These findings demonstrate the significant potential of BSF larvae in managing fruit and vegetable waste while minimizing environmental impact, providing a foundation for further optimization in sustainable waste valorization systems.